Elastic anisotropy, thermal conductivity and tensile properties of MAX phase V2GaC, Nb2GaC and Ta2GaC: First-principles calculations. (March 2023) - Fan, Shanming; Peng, Mingjun; Yang, Ancang; Duan, Yonghua; Qi, Huarong; Wang, Xiaoqi; Yao, Ji; Li, Mengnie; zheng, Shanju
Abstract: MAX phase series materials have excellent thermal, electrical and mechanical properties, and have great research potential. In this work, the structural characteristics, elastic anisotropy, thermal and phonon properties of hexagonal M2 GaC (M = V, Nb and Ta) compounds were calculated using the first-principle calculation method. The stress-strain method and Voigt-Reuss-Hill approximation are used to determine the elastic properties of single crystals and polycrystals, respectively. By calculating the formation enthalpy, it is found that M2 GaC compounds are stable. Meanwhile, these M2 GaC are brittle materials with respect to Poisson's ratio, G H /B H and Cauchy pressure. The elastic anisotropy of M2 GaC is illustrated by the elastic anisotropy index, three-dimension (3D) surface configuration and two-dimension (2D) projection, the order of elastic anisotropy is Nb2 GaC > Ta2 GaC > V2 GaC. Finally, the sound velocity, Debye temperature, thermal conductivity and anisotropy are discussed to provide theoretical support for further study of MAX phase compounds. Graphical abstract: Image 1 Highlights: M2 GaC (M = V, Nb, and Ta) compounds have elastic anisotropy with a sequence of Nb2 GaC > Ta2 GaC > V2 GaC. Minimum thermal conductivities of V2 GaC, Nb2 GaC and Ta2 GaC are 1.596, 1.928, and 1.165 W m −1  K −1, respectively. The hexagonal M2 GaC (M = V, Nb and Ta) compounds are not potential superhard materials. M2 GaC (M = V, Nb, Ta) have no imaginary frequency, indicating that they can exist stably.